PENGARUH KECERDASAN EMOSIONAL, PELATIHAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. MATA AIR BOGA LESTARI - Tri Lestari. S; Rivera Pantro Sukma (Human Capital Development, 2019)
Purpose- The purpose of this research is to know the emotional intelligence (X1), training (X2), and workplace environment (X3) effected partially and simultaneously on employee performance (Y). Design/methodology/approach- The population are the employees of PT. Mata Air Boga Lestari. The sample that used for this research are 100 employees, by accidental sampling technique. Data collection method used by a questionnaire. Data analysis tools that used this research are validity test, reliability test, classic assumption test (normality test, multicolinearity test, heteroscedasticity test, and linearity test), multilinear regression. While the hypotheses testing by F test, t test, partial correlation analysis and coefficient of determination (R2). Findings- From the analysis and discussions it was found that emotional intelligence, training, and workplace environment have a positive effect on employee performance, both partially and simultaneously.